Zinc finger knuckle genes are associated with tolerance to drought and dehydration in chickpea (Cicer arietinum L.) - Khassanova, Gulmira; Oshergina, Irina; Ten, Evgeniy; Jatayev, Satyvaldy; Zhanbyrshina, Nursaule; Gabdola, Ademi; Gupta, Narendra K.; Schramm, Carly; Pupulin, Antonio; Philp-Dutton, Lauren; Anderson, Peter; Sweetman, Crystal; et al. (Frontiers in Plant Science, 2024)
Chickpea (Cicer arietinum L.) is a very important food legume and needs improved drought tolerance for higher seed production in dry environments. The aim of this study was to determe diversity and genetic polymorphism in Zinc finger knuckle genes with CCHC domains and their functional analysis for practical improvement of chickpea breeding. Two CaZF-CCHC genes, Ca04468 and Ca07571, were identified as potentially important candidates associated with plant responses to drought and dehydration. These genes were studied for genetic polymorphism among a set of chickpea accessions, and one SNP was selected for further study from four identified SNP between the promoter regions of each of the two genes. Molecular markers were developed for the SNP and verified using the ASQ and CAPS methods. Genotyping of parents and selected breeding lines from two hybrid populations, and SNP positions on chromosomes with haplotype identification, were confirmed using DArT microarray analysis. Differential expression profiles were identified in the parents and the hybrid populations under gradual drought and rapid dehydration. The SNP-based genotypes were differentially associated with seed weight per plant but not with 100 seed weight. The two developed and verified SNP molecular markers for both genes, Ca04468 and Ca07571, respectively, could be used for marker-assisted selection in novel chickpea cultivars with improved tolerance to drought and dehydration.